A method for treating azo dyes using iron-based amorphous-nanocrystalline dual-phase composite materials
By using iron-based amorphous-nanocrystalline biphasic composite materials as catalysts, combined with chemical precipitation method and mechanical stirring technology, the problem of low degradation efficiency of high-concentration azo dyes in the existing technology is solved, and a rapid and efficient degradation effect is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202410582894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-05-11
AI Technical Summary
The prior art has low degradation efficiency and long time when treating wastewater of high concentration azo dyes, and the research mainly focuses on concentrations below 350mg/L. Effective degradation of high concentration azo dyes above 350mg/L is still not possible.
The iron-based amorphous-nanocrystalline biphasic composite material is used as a catalyst to prepare the material by chemical precipitation method, chemical precipitation method after pickling or chemical precipitation method after annealing, and hydrogen peroxide is added at different pH values and temperatures, and degraded by mechanical stirring. The step-by-step degradation method is used to improve efficiency.
The rapid and efficient degradation of high-concentration azo dyes is achieved, and the degradation of high-concentration azo dyes of 400 mg/L or above can be completed within 6 minutes, with a decolorization rate of more than 95%. This method is suitable for common commercially available iron-based amorphous strips and waste strips.
Smart Images

Figure CN118454675B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, in particular to a method for treating azo dyes by utilizing an iron-based amorphous-nanocrystalline dual-phase composite material. Background Art
[0002] Dye molecules are generally composed of a chromophore that gives them color and an auxochrome that enhances the color of the chromophore. Dyes can be divided into azo, sulfide, methine, indigo and heterocyclic types according to the chromophores or chemical structures they contain. Among them, azo dyes are widely used in the printing and dyeing industry due to their high chroma, stable chemical properties and good coloring. With the rapid growth of the output of printing and dyeing products, the discharge of a large amount of printing and dyeing wastewater has caused serious harm to the environment, ecology and human health. The concentration of organic pollutants in printing and dyeing wastewater is generally high, among which the COD of pure cotton, chemical fiber, pure silk and wool printing and dyeing wastewater is 2.3477 W / m2. cr Generally, it is between 150-1500 mg / L. It is extremely important for the treatment of azo dye printing and dyeing wastewater.
[0003] Advanced oxidation technology is a commonly used technology in the treatment of printing and dyeing wastewater, including ozone oxidation, electrochemical oxidation, flocculation-sedimentation, Fenton and Fenton-like oxidation, etc. Among them, Fenton-like oxidation has the advantages of fast oxidation reaction speed, high catalytic degradation efficiency, and the ability to convert organic molecules into CO 2 and H 2 The advantages of small molecules such as O are expected to fundamentally eliminate toxic and harmful substances in printing and dyeing wastewater. The Fenton-like oxidation method generally adds hydrogen peroxide, iron powder or iron-based amorphous alloy to the acidic system, and generates hydroxyl radicals through the reaction of hydrogen peroxide and hydrogen ions with zero-valent iron in the system, thereby further degrading organic molecules in the wastewater system. This method has a significant effect on the degradation of azo dyes.
[0004] However, the concentration of azo dyes degraded by Fenton-like oxidation methods is generally tens of milligrams per liter, and there are few studies and reports on the degradation of high-concentration azo dyes (above 100 mg / L) wastewater. In addition, the time required for the Fenton-like oxidation method to degrade an aqueous azo dye solution with a concentration of tens of milligrams per liter is generally tens to hundreds of minutes.
[0005] At present, the published research on the catalytic degradation of azo dye wastewater using iron-based amorphous strips includes:
[0006] Chinese patent CN 114604958 provides a method for catalytically degrading acid orange 7 using an iron-based amorphous composite material, but the concentration of the azo dye degraded is 20-100 mg / L, and the time required for the decolorization rate to reach 90% is about 20 minutes.
[0007] Chinese patent CN 107326159 discloses a method for preparing an iron-based nanocrystalline alloy and degrading an aqueous solution of Golden Orange 2. However, after the iron-based nanocrystalline alloy prepared by the method degraded a 100 mg / L aqueous solution of Golden Orange 2 for 60 minutes, the decolorization rate was only 84%.
[0008] Chinese patent CN 114988551 discloses a method for ultrasonically assisted iron-based amorphous coating to degrade acid orange II or golden orange II. When 28kHz ultrasonic wave is used to degrade 100 mg / L acid orange II aqueous solution for 10 minutes, the decolorization rate can reach 95%. However, this method requires ultrasonic assistance, the equipment is relatively complex, and the range of catalytic degradation of azo dyes is 20-100 mg / L. The application and degradation effect of this method on high-concentration azo dyes have not been seen.
[0009] Chinese patent CN 115849544 discloses a method for removing azo dyes by strengthening an iron-based amorphous alloy with pyrite, but this method only has the effect of promoting degradation when the concentration of azo dye wastewater is 10-100 mg / L, which is reflected in reducing the degradation time.
[0010] Chinese patent CN 114807661 discloses a method for preparing a porous iron-based amorphous / copper dual alloy composite material and its application in degrading Orange II. By preparing a composite material with specific composition and structure, the degradation time of Orange II is shortened. However, the decolorization rate of this method after degrading a 40 mg / L dye aqueous solution for 5 minutes is less than 76%.
[0011] In addition, Chinese patents CN 116351435, CN 115041204 and CN115414953 improve the performance of the strips in catalytic degradation of azo dyes by adjusting the composition and microstructure of the iron-based amorphous strips, but these methods only have a gain effect on the degradation efficiency of aqueous solutions of azo dyes at 120 mg / L and below.
[0012] Chinese patent CN 103896388 discloses a method for treating Orange G using a dual catalyst of zero-valent iron particles and nano-copper oxide. However, the COD of the wastewater after treatment is cr The decolorization rate is 120-300 mg / L, and the decolorization rate is less than 80% after 40 minutes of degradation.
[0013] Chinese patent CN 102070236 discloses the preparation of an iron-based amorphous alloy strip and its application in degrading a direct blue 2B dye aqueous solution, but the decolorization rate of the iron-based amorphous alloy strip after treating a 200 mg / L direct blue 2B aqueous solution for 60 minutes is less than 80%.
[0014] Chinese patent CN 206476788 discloses a solar-driven iron-based amorphous device for degrading Acid Orange II. However, after the device treated a 200 mg / L Orange II aqueous solution for 40 minutes, the decolorization rate was still less than 90%.
[0015] In summary, the current degradation efficiency of azo dyes using iron-based amorphous materials is low. Even after auxiliary means are used to strengthen the iron-based amorphous strips, the time required for the degradation of azo dyes is still relatively long. In addition, research on the treatment of azo dyes with iron-based amorphous materials is limited to the degradation of aqueous solutions with azo dye concentrations below 350 mg / L. Effective degradation of high-concentration azo dye wastewater above 350 mg / L has not yet been achieved. Summary of the invention
[0016] The purpose of the present invention is to provide a method for treating azo dyes using an iron-based amorphous-nanocrystalline dual-phase composite material to solve the problems existing in the above-mentioned prior art.
[0017] To achieve the above object, the present invention provides the following solutions:
[0018] The present invention provides an iron-based amorphous-nanocrystalline dual-phase composite material, which is prepared by any one of methods 1 to 3:
[0019] Method 1 (chemical precipitation method): immersing the iron-based amorphous strip in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material;
[0020] Method 2 (chemical precipitation method after pickling): pickling the iron-based amorphous strip and then immersing it in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material;
[0021] Method 3 (chemical precipitation method after annealing): The iron-based amorphous strip is placed in a vacuum of not less than 5×10 -3 The method is annealed at 450-900° C. in a vacuum environment of 0.04 Pa, cooled to room temperature, and immersed in a copper salt aqueous solution at 10-80° C. to obtain the iron-based amorphous-nanocrystalline dual-phase composite material.
[0022] As a further preferred embodiment of the present invention, in the methods 1 to 3, the copper salt comprises one or more of copper chloride, copper sulfate, basic copper sulfate, copper persulfate and the above copper salt compounds that can be obtained by chemical reaction, and the concentration of the copper salt aqueous solution is 0.05-1.5 mol / L, more preferably 0.2-1.0 mol / L;
[0023] As a further preferred embodiment of the present invention, the mass percentage of iron atoms in the iron-based amorphous strip is above 70%, and more preferably, the mass percentage of iron atoms in the commercially available iron-based amorphous strip is 84-95%.
[0024] As a further preferred embodiment of the present invention, the acid solution used for pickling in the second method includes one or more of sulfuric acid, hydrochloric acid, nitric acid, hypochlorous acid and the like; the mass concentration of the acid solution is 1-30%, more preferably 5-15%.
[0025] As a further preferred embodiment of the present invention, the annealing time in the method three is 10-30 minutes.
[0026] The present invention provides a method for treating low-concentration azo dyes by using the iron-based amorphous-nanocrystalline dual-phase composite material as a catalyst, comprising the following steps:
[0027] The pH of the low-concentration azo dye aqueous solution is adjusted to 2-6.5, the temperature is adjusted to 10-80°C, 1-500mmol / L of hydrogen peroxide is added, and then the iron-based amorphous-nanocrystalline dual-phase composite material is added to the azo dye aqueous solution in an amount of 0.25-25g / L for degradation.
[0028] As further preferred embodiment of the present invention, the azo dye includes any one or more of Orange II, methylene blue, rhodamine B, and methyl orange.
[0029] As a further preferred embodiment of the present invention, the low-concentration azo dye is an azo dye solution with a concentration of 10-350 mg / L.
[0030] As a further preference of the present invention, the degradation time is 30-600s.
[0031] The present invention also provides a method for treating high-concentration azo dyes in steps using the iron-based amorphous-nanocrystalline dual-phase composite material as a catalyst, comprising the following steps:
[0032] The pH of a high-concentration azo dye aqueous solution is adjusted to 2-6.5, the temperature is adjusted to 10-80°C, 1-500 mmol / L of hydrogen peroxide is added, and then the iron-based amorphous-nanocrystalline dual-phase composite material is added to the azo dye aqueous solution in an amount of 0.25-25 g / L. After the first degradation is completed through mechanical stirring, the azo dye aqueous solution is filtered, and then the pH is readjusted to 2-6.5, 1-500 mmol / L of hydrogen peroxide is added, the temperature is adjusted to 10-80°C, and the filtrate is degraded again using the iron-based amorphous-nanocrystalline dual-phase composite material.
[0033] As further preferred embodiment of the present invention, the azo dye includes any one or more of Orange II, methylene blue, rhodamine B, and methyl orange.
[0034] As a further preferred embodiment of the present invention, the high concentration azo dye is an azo dye solution with a concentration of 350-1000 mg / L.
[0035] As a further preference of the present invention, the speed of the mechanical stirring is 60-4500 r / min.
[0036] As a further preference of the present invention, the first degradation time is 30-600s.
[0037] As a further preferred embodiment of the present invention, the filtration after degradation can be carried out by one of normal pressure filtration, reduced pressure filtration and hot filtration, and one or more of sodium hydroxide, sodium carbonate and sodium bicarbonate can be added before filtration to form a precipitate. More preferably, the filtration after degradation is carried out by reduced pressure filtration, and one or more of sodium hydroxide, sodium carbonate and sodium bicarbonate can be added before filtration to form a precipitate.
[0038] As a further preferred embodiment of the present invention, when the filtrate is degraded again with the iron-based amorphous-nanocrystalline, the iron-based amorphous-nanocrystalline can be the iron-based amorphous-nanocrystalline strips used for the first degradation and washed with deionized water, or a new iron-based amorphous-nanocrystalline two-phase composite material can be obtained. More preferably, when the filtrate is degraded again with the iron-based amorphous-nanocrystalline, a new iron-based amorphous-nanocrystalline two-phase composite material is obtained.
[0039] Compared with the commercially available iron-based amorphous strips, the iron-based amorphous-nanocrystalline dual-phase composite material prepared by the chemical precipitation method, the chemical precipitation method after pickling or the chemical precipitation method after annealing in the present invention has a more complex microstructure. The surface of the strip is affected by the nanocrystals to form a potential difference in different areas, which is beneficial to increase the rate and amount of zero-valent iron formed by the strip in the Fenton-like reaction, thereby accelerating the degradation reaction of the azo dye. Fig. 9 As shown. Fig. 9 (a) shows the redox reaction that occurs during the degradation of azo dyes on the surface of commercially available iron-based amorphous ribbons: First, the iron in the iron-based amorphous ribbon loses electrons to form Fe 2+ ; then under acidic conditions Fe 2+ With H 2 O 2 The reaction generates hydroxyl radicals, which react with azo dye molecules to complete the degradation, see formula (1) and (2). However, Fe 3+ Also with H 2 O 2 Further reaction generates peroxy hydroxyl groups, thereby greatly reducing the generation of hydroxyl radicals and subsequent degradation of azo dyes, as shown in formula (3).
[0040] For the dual-phase composite material prepared by chemical precipitation method, the iron atoms on the surface of the strip undergo redox reaction and enter the salt solution, thereby forming micron or nano pitting pits on the surface of the strip, increasing the specific surface area of the strip; at the same time, the copper ions in the solution undergo replacement reaction with the iron in the strip to form nanocrystals on the surface of the strip, and the copper ions in the solution react with the iron in the strip to provide more positions and active sites for the adsorption and degradation of azo dyes, such as Fig. 9 (b) In addition, a large number of galvanic groups between copper nanocrystals and iron-based amorphous materials are formed on the surface of the strip, which not only accelerates the anode Fe 2+ The formation of Fe 3+ The electrons are reduced to Fe 2+ , thereby reducing the formation of peroxy hydroxyl groups, and the peroxy hydroxyl groups generated in the solution will react with H + Regenerate H 2 O 2 , thus ensuring the H 2 O 2 The concentration and degradation reaction proceed as shown in formulas (4)-(6). Fig. 9 Eq.1-6 correspond to formulas (1)-(6) respectively.
[0041] Fe 2+ +H 2 O 2 +H + →Fe 3+ +H 2 O+·OH· (1)
[0042] organics+·OH→products (2)
[0043] Fe 3+ +H 2 O 2 →Fe 2+ +·O 2 H+H + (3)
[0044] Fe 3+ +e - →Fe 2+ (4)
[0045] 2H + +2e - →H 2 (5)
[0046] ·O 2 H+H + +e - →H 2 O2 (6)
[0047] During the formation of the iron-based amorphous-nanocrystalline dual-phase composite material, the possible reactions of the strips in the copper salt and acid solution are:
[0048] 2H + +Fe→Fe 2+ +H 2 (7)
[0049] Cu 2+ +Fe→Fe 2+ +Cu (8)
[0050] In addition, when the annealed iron-based amorphous strip undergoes chemical precipitation reaction, the nanocrystals (usually α-Fe phase) formed on the strip surface due to annealing can not only increase the rate of chemical precipitation (chemical formula (7)-(8)), but also the interface between the strip and the α-Fe phase or the precipitated nanocrystals can prevent the formation of a continuous passivation film on the strip surface, thereby improving the strip's ability to continuously generate zero-valent iron, thereby preventing the strip from blackening during the degradation of high-concentration azo dyes, such as Figures 5 to 7 As shown in (Example 5, Example 6 and Example 7); directly using iron-based amorphous strips to degrade high-concentration azo dyes is prone to blackening, such as Fig.12 and 13 As shown (Comparative Example 3 and Comparative Example 4).
[0051] In the present invention, filtering the azo dye after the first degradation can prevent high-concentration azo dye and its reaction products from covering or precipitating on the strip surface, thereby maintaining a high catalytic degradation rate of the iron-based amorphous-nanocrystalline dual-phase composite material.
[0052] The present invention discloses the following technical effects:
[0053] (1) The surface of the iron-based amorphous-nanocrystalline dual-phase composite material prepared in the present invention is affected by nanocrystals, and the potential difference formed in different regions can increase the formation rate and amount of zero-valent iron; and the nanocrystals increase the specific surface area of the strips, providing more active sites for dye adsorption and degradation; in addition, the amorphous-nanocrystalline interface can prevent the formation of a continuous passivation film on the strip surface, improve the ability to continuously generate zero-valent iron, and effectively prevent the occurrence of blackening and other phenomena during dye degradation.
[0054] (2) The present invention realizes the rapid and efficient degradation of high-concentration azo dyes by preparing the iron-based amorphous-nanocrystalline dual-phase composite material through the iron-based amorphous strips, and the amorphous-nanocrystalline dual-phase composite material has low preparation cost, simple process, simple equipment requirements, and is suitable for common commercially available iron-based amorphous strips and waste iron-based amorphous strips with a passivation film or an oxide film formed on the surface.
[0055] (3) The present invention utilizes an iron-based amorphous-nanocrystalline dual-phase composite material to step-by-step degrade (filter and degrade again after primary degradation) a mixed aqueous solution of azo dyes, and can complete the degradation of 400 mg / L and above high-concentration azo dye wastewater within 6 minutes, with a decolorization rate of more than 95%. Using 4-8 g / L of an iron-based amorphous-nanocrystalline dual-phase composite material, a decolorization rate of 98% of a 400-800 mg / L mixed dye can be achieved within 4 minutes.
[0056] (4) The method of the present invention can achieve the degradation of high-concentration azo dyes at room temperature without auxiliary light or electric field conditions. The amount of chemical reagents required to be added during the treatment process is small, the price is low, and the operation is easy. The precipitate after filtration is easy to recover and process. This method has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0058] Figure 1 The UV-visible absorption spectra of a 400 mg / L mixed dye aqueous solution (100 mg / L each of methyl orange, orange II, methylene blue and rhodamine B dyes) treated with the iron-based amorphous-nanocrystalline dual-phase composite material in Example 1 at different times (a) and the decolorization of the dye solution at different times (b).
[0059] Figure 2 The UV-visible absorption spectra of a 400 mg / L mixed dye aqueous solution (100 mg / L each of methyl orange and orange II, 40 mg / L of methylene blue, and 160 mg / L of rhodamine B dye) treated with the iron-based amorphous-nanocrystalline dual-phase composite material in step-by-step manner (first degradation and filtration for 4 min before degradation) in Example 2 after different time periods (a) and the decolorization of the dye solution at different time periods (b).
[0060] Figure 3 The UV-visible absorption spectra of an 800 mg / L mixed dye aqueous solution (200 mg / L each of methyl orange, orange II, methylene blue and rhodamine B dyes) treated with the iron-based amorphous-nanocrystalline dual-phase composite material in step-by-step manner (filtered and degraded again after the first degradation for 1 min) in Example 3 at different times (a) and the decolorization of the dye solution at different times (b).
[0061] Figure 4The UV-visible absorption spectra of the 320 mg / L mixed dye aqueous solution (80 mg / L each of methyl orange, orange II, methylene blue and rhodamine B dyes) treated with the iron-based amorphous-nanocrystalline dual-phase composite material in Example 4 at different times (a) and the decolorization of the dye solution at different times (b).
[0062] Figure 5 The UV-visible absorption spectra of 80 mg / L Orange II aqueous solution directly degraded by the iron-based amorphous-nanocrystalline dual-phase composite material prepared by chemical precipitation method after annealing in Example 5 at different times (a) and the decolorization of the dye solution at different times (b).
[0063] Figure 6 The UV-visible absorption spectra of the iron-based amorphous-nanocrystalline dual-phase composite material prepared by chemical precipitation after acid washing in Example 6 degrading 100 mg / L Orange II aqueous solution at different times (a) and the decolorization of the dye solution at different times (b).
[0064] Figure 7 The UV-visible absorption spectra of the iron-based amorphous-nanocrystalline dual-phase composite material prepared by the chemical precipitation method in Example 7 degrading 100 mg / L Orange II aqueous solution at different times (a) and the decolorization of the dye solution at different times (b).
[0065] Figure 8 Typical SEM photos of the surface of the amorphous-nanocrystalline dual-phase composite material of 1K107 strip prepared according to the method of the present invention: morphology of the strip after annealing in Example 5 (a), morphology of the strip after chemical precipitation in Example 5 (b), morphology of the strip after acid washing and chemical precipitation in Example 6 (c), morphology of the strip after direct chemical precipitation in Example 7 (d).
[0066] Fig. 9 Schematic diagram of the mechanism of degradation of azo dyes by commercially available iron-based amorphous strips (a) and the iron-based amorphous-nanocrystalline dual-phase composite material prepared by the present invention (b).
[0067] Fig.10 The UV-visible absorption spectra of a 400 mg / L mixed dye aqueous solution (100 mg / L each of methyl orange, orange II, methylene blue and rhodamine B dyes) treated with an iron-based amorphous-nanocrystalline dual-phase composite material (only filtered after the first degradation) in Comparative Example 1 at different times (a) and the decolorization of the dye solution at different times (b).
[0068] Fig.11The UV-visible absorption spectra of 320 mg / L mixed dye aqueous solution (80 mg / L each of methyl orange, orange II, methylene blue and rhodamine B dyes) treated with the iron-based amorphous-nanocrystalline dual-phase composite material in Comparative Example 2 (degraded only once, without filtration and re-degradation) at different times (a) and the decolorization of the dye solution at different times (b).
[0069] Fig.12 The UV-visible absorption spectra of the 80 mg / L Orange II aqueous solution directly treated with the iron-based amorphous strips in Comparative Example 3 after different time periods (a) and the decolorization of the dye solution at different time periods (b).
[0070] Fig.13 The UV-visible absorption spectra of the 100 mg / L Orange II aqueous solution directly treated with the iron-based amorphous strips in Comparative Example 4 after different time periods (a) and the decolorization of the dye solution at different time periods (b). DETAILED DESCRIPTION
[0071] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0072] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0073] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0074] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0075] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0076] Example 1
[0077] In this example, a commercially available iron-based amorphous strip was used to prepare an iron-based amorphous-nanocrystalline dual-phase composite material by chemical precipitation, and then a mixed azo dye with a concentration of 400 mg / L was treated step by step. The details are as follows:
[0078] (1) 1 g of commercially available 1K107 strip was placed in 15 mL of a 0.2 mol / L copper sulfate aqueous solution and allowed to stand at 45°C for 10 min. After being taken out, an iron-based amorphous-nanocrystalline dual-phase composite material prepared by a chemical precipitation method was obtained.
[0079] (2) Take 25 mL of 1000 mg / L methyl orange, orange II, methylene blue and rhodamine B dyes, add them to 150 mL of deionized water and mix them to obtain 250 mL of 400 mg / L azo dye aqueous solution, add 180 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 2.9, and place in a 35°C water bath and keep warm for 10 min.
[0080] (3) The mixed solution was stirred mechanically at 2000 r / min, 1 g of an iron-based amorphous-nanocrystalline dual-phase composite material (4 g / L) was added, the water bath temperature was maintained at 35 °C, and 4.8 mL of the mixed azo dye aqueous solution was taken before adding the strips and at 0.5 min, 1 min, 2 min, 3 min, and 5 min after adding the strips, respectively, and filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane.
[0081] (4) Use filter paper to filter the mixed solution that has been degraded for 5 minutes at normal pressure, add 1 g of the washed iron-based amorphous-nanocrystalline dual-phase composite material (4 g / L) to the filtrate, put the beaker containing the filtrate into a 35°C water bath and continue stirring at 2000 r / min, and take 4.8 mL of the mixed azo dye aqueous solution at 10 minutes, 20 minutes, 30 minutes, and 40 minutes after the iron-based amorphous-nanocrystalline dual-phase composite material is added again (also calculated from the first addition of the strip as the starting point), and filter through a 0.22 μm water-based polyethersulfone (PES) filter membrane.
[0082] The solution spectrum was measured using a UV-visible photometer, and the color change of the dye solution over time was recorded by taking photos. The decolorization rate of the azo dye in the solution at different times was calculated and the decolorization rate curve was drawn.
[0083] The ultraviolet visible light absorption spectrum measured in this embodiment is as follows Figure 1 As shown in (a), Figure 1(a) shows that the mixed azo dyes are rapidly degraded and decolorized under the degradation conditions. Figure 1 (b) It can be seen that after 0.5 minutes of reaction, almost all the azo dye molecules in the aqueous solution have completed the reaction, and the decolorization rate is 99.8%. As the reaction time continues, the decolorization rate in the aqueous solution decreases, and it drops to 90.4% at 5 minutes. The reason is that the concentration of the product generated by the previous degradation reaction is high, and it precipitates and adheres to the surface of the strip, causing the rate of zero-valent iron generation in the strip to decrease. After the solution is filtered and degraded, the azo dye in the solution is further degraded, and the decolorization rate reaches 99.4% again, and it remains at 98.9-99.7% in the next 40 minutes.
[0084] from Figure 1 As can be seen from the curve (b), filtering and then degrading the azo dye aqueous solution after the first degradation can prevent the reverse reaction during the degradation of the azo dye, and can quickly achieve and maintain a decolorization rate of about 99% for high-concentration azo dyes.
[0085] Example 2
[0086] In this example, a commercially available iron-based amorphous strip was used to prepare an iron-based amorphous-nanocrystalline dual-phase composite material by chemical precipitation, and then a mixed azo dye with a concentration of 400 mg / L was treated step by step. The details are as follows:
[0087] (1) 1 g of commercially available 1K107 strip was placed in 15 mL of an aqueous solution of copper sulfate and copper persulfate in a molar ratio of 2:1 (total concentration 0.3 mol / L), and allowed to stand at 40°C for 5 min. After being taken out, an iron-based amorphous-nanocrystalline dual-phase composite material prepared by a chemical precipitation method was obtained.
[0088] (2) Take 25 mL each of 1000 mg / L methyl orange and orange II, 10 mL of 1000 mg / L methylene blue, and 40 mL of 1000 mg / L rhodamine B dye, add them to 150 mL of deionized water and mix them to obtain 250 mL of 400 mg / L azo dye aqueous solution, add 180 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place in a 25°C water bath to keep warm for 10 min.
[0089] (3) The mixed solution was mechanically stirred at 2000 r / min, 1 g of the iron-based amorphous-nanocrystalline dual-phase composite material (4 g / L) obtained in step (1) was added, the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before and 0.5 min after the addition of the strips, respectively, and filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane.
[0090] (4) Use filter paper to filter the mixed solution that has been degraded for 0.5 min at normal pressure, place the beaker containing the filtrate in a 25°C water bath and continue stirring using a mechanical stirrer at 2000 r / min, take 4.8 mL of the mixed azo dye aqueous solution at 1 min, 2 min, 3 min, 4 min, 5 min, and 6 min after filtration, respectively, add 1 g of the washed strip after the 4th minute, readjust the pH to 3, and add 90 mmol / L hydrogen peroxide. The taken 4.8 mL of the azo dye aqueous solution is filtered through a 0.22 μm water-based polyethersulfone (PES) filter membrane.
[0091] The solution spectrum was measured using a UV-visible photometer, and the color change of the dye solution over time was recorded by taking photos. The decolorization rate of the azo dye in the solution at different times was calculated and the decolorization rate curve was drawn.
[0092] The ultraviolet visible light absorption spectrum measured in this embodiment is as follows Figure 2 As shown in (a), the mixed azo dyes are rapidly degraded and decolorized under the degradation conditions. Figure 2 (b) It can be seen that after 0.5 min of reaction, the mixed azo dye has been basically degraded, and the decolorization rate is 99.6%. The decolorization rate of the filtrate after filtration decreases slightly, which is similar to the situation in Comparative Example 1; after the strips are added to the filtrate for re-degradation, the decolorization rate is maintained at 99.6-99.8%.
[0093] from Figure 2 As can be seen from the curve (b), when the azo dye aqueous solution after the first degradation is filtered, the decolorization rate of the filtrate decreases slightly after 4 minutes, and the decolorization rate of high-concentration azo dyes can be maintained above 99% after further degradation.
[0094] Example 3
[0095] In this example, a chemical precipitation method is used to prepare an iron-based amorphous-nanocrystalline dual-phase composite material from commercially available iron-based amorphous strips, and then a mixed azo dye with a concentration of 800 mg / L is degraded after filtration. The specific operation steps are as follows:
[0096] (1) 2 g of commercially available 1K107 strip was placed in 30 mL of an aqueous solution of copper sulfate and copper chloride in a molar ratio of 3:1 (total concentration 0.2 mol / L), and allowed to stand at 45°C for 10 min. After being taken out, an iron-based amorphous-nanocrystalline dual-phase composite material prepared by a chemical precipitation method was obtained.
[0097] (2) Take 50 mL of 1000 mg / L methyl orange, orange II, methylene blue and rhodamine B dyes, add them to 50 mL of deionized water and mix them to obtain 250 mL of 800 mg / L azo dye aqueous solution, add 180 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place in a 25°C water bath and keep warm for 10 min.
[0098] (3) The mixed solution was mechanically stirred at 2000 r / min, 2 g of the iron-based amorphous-nanocrystalline dual-phase composite material (8 g / L) obtained in step (1) was added, the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before and 0.5 min after the addition of the strips, respectively, and filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane.
[0099] (4) Use filter paper to filter the mixed solution that has been degraded for 0.5 min at normal pressure, put it into a 25°C water bath, add 2 g of the washed strip (8 g / L), readjust the pH to 3, add 180 mmol / L hydrogen peroxide, and continue stirring with a mechanical stirrer at 2000 r / min. Take 4.8 mL of the mixed azo dye aqueous solution at 2 min, 3 min, and 6 min after the strip is re-added, and filter it through a 0.22 μm water-based polyethersulfone (PES) filter membrane.
[0100] (5) Use a UV-visible photometer to measure the solution spectrum, take photos to record the color change of the dye solution over time, calculate the decolorization rate of the azo dye in the solution at different times and draw a decolorization rate curve.
[0101] The ultraviolet visible light absorption spectrum measured in this embodiment is as follows Figure 3 As shown in (a), the mixed azo dyes are rapidly degraded and decolorized under the degradation conditions. Figure 3 (b) It can be seen that after 0.5 min of reaction, the mixed azo dye has been basically degraded, and its decolorization rate is 98.9%; after 800 mg / L of azo dye is filtered and added to the strip for further degradation, the decolorization rate is 98.4% after 6 min.
[0102] from Figure 3 As can be seen from the curve (b), the high-concentration azo dyes treated in steps can quickly achieve and maintain a decolorization rate of more than 98% for the azo dyes.
[0103] Example 4
[0104] The difference between this embodiment and embodiment 3 is only that:
[0105] In this embodiment, the total concentration of the mixed azo dye is 320 mg / L, that is, the concentration of each azo dye is 80 mg / L; 10 mL of an aqueous solution of copper sulfate and copper chloride in a molar ratio of 1:1 (total concentration 0.1 mol / L) is used to soak 1 g of commercially available 1K107 strip for 20 min. 1 g of iron-based amorphous-nanocrystalline dual-phase composite material (4 g / L) is used for both primary degradation and secondary degradation after filtration. 4.8 mL of the mixed azo dye aqueous solution is taken at 0.5 min, 1 min, 2 min, and 3 min after the strip is re-added, and then filtered through a 0.22.2 water-based polyethersulfone (PES) filter membrane for photography and UV-visible photometer testing.
[0106] The ultraviolet visible light absorption spectrum measured in this embodiment is as follows Figure 4 As shown in (a), the mixed azo dyes are rapidly degraded and decolorized under the degradation conditions. Figure 4 (b) It can be seen that the decolorization rate of the mixed azo dye after 0.5 min of reaction is 95.3%; after 320 mg / L of azo dye is filtered and added to the strips for further degradation, the decolorization rate is 98.1-98.7%.
[0107] Examples 5, 6 and 7 are used to illustrate that when the amorphous-nanocrystalline material prepared by the present invention treats low concentration (80-100 mg / L) azo dyes, a high decolorization rate can be achieved without step-by-step treatment, and no blackening phenomenon occurs:
[0108] Example 5
[0109] In this example, an iron-based amorphous-nanocrystalline dual-phase composite material was prepared from commercially available iron-based amorphous ribbons by chemical precipitation after annealing, and 80 mg / L Orange II aqueous solution was directly treated.
[0110] The specific steps are as follows:
[0111] (1) Take 0.15 g of commercially available 1K107 strip and place it in a vacuum heat treatment system at a vacuum degree of 4 × 10 -3 In a vacuum environment of 1.5 Pa, the Fe-based amorphous strips were isothermally annealed at 460 °C for 20 min and then cooled to room temperature.
[0112] (2) After annealing, 0.15 g of the strip was taken out and placed in 10 mL of a 0.1 mol / L copper sulfate aqueous solution, and allowed to stand at 45° C. for 20 min. After taking out, an iron-based amorphous-nanocrystalline dual-phase composite material prepared by a chemical precipitation method was obtained.
[0113] (3) Take 20 mL of 1000 mg / L Orange II solution, add it to 230 mL of deionized water, mix it and obtain 250 mL of 80 mg / L Orange II aqueous solution, add 90 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place it in a 25°C water bath and keep it warm for 10 min.
[0114] (4) The mixed solution was mechanically stirred at 2000 r / min, 0.15 g of the iron-based amorphous-nanocrystalline dual-phase composite material (0.6 g / L) obtained in step (2) was added, the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before adding the strips and at 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 8 min, 10 min, and 15 min after adding the strips, and filtered through a 0.22.2 water-based polyethersulfone (PES) filter membrane.
[0115] (5) Use a UV-visible photometer to measure the solution spectrum, take photos to record the color change of the dye solution over time, calculate the decolorization rate of the azo dye in the solution at different times and draw a decolorization rate curve.
[0116] The ultraviolet visible light absorption spectrum measured in this embodiment is as follows Figure 5 As shown in (a), the figure shows that Orange II dye degrades and decolorizes rapidly under this degradation condition. Figure 5 (b) It can be seen that after 4 minutes of reaction, the decolorization rate of Orange II dye is 94.7%, and then the decolorization rate of the dye aqueous solution increases slightly with time. After 10 minutes of degradation, the decolorization rate reaches 99.9%, and no blackening occurs in Comparative Examples 3 and 4. Fig.12 and Fig.13 ) situation.
[0117] Example 6
[0118] In this example, an iron-based amorphous-nanocrystalline dual-phase composite material was prepared from commercially available iron-based amorphous strips by chemical precipitation after pickling, and a 100 mg / L Orange II aqueous solution was directly treated.
[0119] The specific steps are as follows:
[0120] (1) 0.25 g of commercially available 1K107 strip was placed in 10 mL of 5% dilute sulfuric acid, allowed to stand at 45°C for 10 s, taken out and placed in 10 mL of 0.1 mol / L copper sulfate aqueous solution, allowed to stand at 45°C for 5 s, and taken out to obtain an iron-based amorphous-nanocrystalline dual-phase composite material prepared by a chemical precipitation method.
[0121] (2) Take 25 mL of 1000 mg / L Orange II solution, add it to 225 mL of deionized water, mix it and obtain 250 mL of 100 mg / L Orange II aqueous solution, add 180 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place it in a 25°C water bath and keep it warm for 10 min.
[0122] (3) The mixed solution was mechanically stirred at 2000 r / min, 0.25 g of the iron-based amorphous-nanocrystalline dual-phase composite material (1 g / L) obtained in step (1) was added, the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before adding the strips and at 0.5 min, 1 min, 2 min, 3 min, 6 min, 9 min, 17 min and 25 min after adding the strips, respectively, and filtered through a 0.22.2 water-based polyethersulfone (PES) filter membrane.
[0123] (4) Use a UV-visible photometer to measure the solution spectrum, take photos to record the color change of the dye solution over time, calculate the decolorization rate of the azo dye in the solution at different times and draw a decolorization rate curve.
[0124] The ultraviolet visible light absorption spectrum measured in this embodiment is as follows Figure 6 As shown in (a), the figure shows that Orange II dye degrades and decolorizes rapidly under this degradation condition. Figure 6 (b) It can be seen that the decolorization rate of Orange II is 92.8% after 1 minute of reaction, 97.5% after 2 minutes of degradation, 99.1% after 3 minutes of degradation, and 99.8% after 25 minutes of reaction, without blackening.
[0125] Example 7
[0126] In this example, a chemical precipitation method was used to prepare an iron-based amorphous-nanocrystalline dual-phase composite material from commercially available iron-based amorphous strips, and a 100 mg / L Orange II aqueous solution was directly treated.
[0127] The specific steps are as follows:
[0128] (1) 0.25 g of commercially available 1K107 strip was placed in 10 mL of 0.1 mol / L copper sulfate aqueous solution and allowed to stand at 45°C for 20 min. After being taken out, an iron-based amorphous-nanocrystalline dual-phase composite material prepared by a chemical precipitation method was obtained.
[0129] (2) Take 25 mL of 1000 mg / L Orange II solution, add it to 225 mL of deionized water, mix it and obtain 250 mL of 100 mg / L Orange II aqueous solution, add 180 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place it in a 25°C water bath and keep it warm for 10 min.
[0130] (3) The mixed solution was mechanically stirred at 2000 r / min, 0.25 g of the iron-based amorphous-nanocrystalline dual-phase composite material (1 g / L) obtained in step (1) was added, the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before adding the strip and at 0.5 min, 1 min, 2 min, 3 min, 6 min, 9 min, 17 min and 25 min after adding the strip, respectively, and filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane.
[0131] (4) Use a UV-visible photometer to measure the solution spectrum, take photos to record the color change of the dye solution over time, calculate the decolorization rate of the azo dye in the solution at different times and draw a decolorization rate curve.
[0132] The ultraviolet visible light absorption spectrum measured in this embodiment is as follows Figure 7 As shown in (a), the figure shows that Orange II dye degrades and decolorizes rapidly under this degradation condition. Figure 7 (b) It can be seen that the decolorization rate of Orange II is 98.8% after 1 minute of reaction, 99.7% after 2 minutes of degradation, 99.8% after 3 minutes of degradation, and 99.7% after 25 minutes of reaction, without blackening.
[0133] This is in sharp contrast to the direct use of commercially available iron-based amorphous strips for degradation in Comparative Examples 3 and 4: even though the amount of iron-based amorphous strips used in Comparative Examples 3 and 4 (4 g / L) is much higher than the amounts used in Examples 5, 6 and 7 (0.6 g / L, 1 g / L and 1 g / L), the degradation effect and decolorization rate of the strips on azo dyes in the comparative examples are poor, indicating that the method provided by the present invention can effectively improve the degradation ability of commercially available iron-based amorphous strips and prevent the occurrence of blackening during the degradation process.
[0134] Figure 8 Typical SEM photos of the surface of the amorphous-nanocrystalline dual-phase composite material of 1K107 strip prepared according to the method of the present invention: morphology of the strip after annealing in Example 5 (a), morphology of the strip after chemical precipitation in Example 5 (b), morphology of the strip after acid washing and chemical precipitation in Example 6 (c), morphology of the strip after direct chemical precipitation in Example 7 (d). Figure 8 It is shown that a large number of nanoparticles are formed on the surface of the strips after the chemical precipitation treatment, and the size and number of the nanoparticles are also affected by the heat treatment, pickling and chemical precipitation treatment time; combined with the catalytic degradation effect and degradation mechanism schematic diagram of Examples 5-7 ( Fig. 9) It is not difficult to find that the number, size and other states of nanoparticles will affect the efficiency of catalytic degradation. It can be seen that the chemical precipitation method proposed in the present invention can not only realize the preparation of iron-based amorphous-nanocrystalline composite materials, but also adjust the chemical precipitation process and regulate the microstructure of nanocrystals on the surface of iron-based amorphous according to the strip composition and actual application conditions, so as to meet the needs of different degradation rates.
[0135] Comparative Examples 1 and 2 are used to illustrate that when the iron-based amorphous-nanocrystalline dual-phase composite material prepared by the present invention treats high-concentration (300 mg / L and above) azo dyes, if precipitation filtration and secondary degradation are not performed, the azo dye decolorization rate will first reach a high level in a short time, and then gradually decrease with time. Fig.10 and Fig.11 shown.
[0136] Comparative Example 1
[0137] This comparative example uses a chemical precipitation method after acid washing to prepare an iron-based amorphous-nanocrystalline dual-phase composite material from a commercially available iron-based amorphous strip, and then filters the aqueous solution after the primary degradation. Combined with Comparative Example 2, it is shown that precipitation filtration can effectively alleviate the reverse reaction rate of high-concentration mixed azo dyes (the decolorization rate decreases with time), but cannot achieve the degradation of high-concentration azo dyes (the decolorization rate is maintained at 98% or above).
[0138] The specific steps are as follows:
[0139] (1) 1 g of commercially available 1K107 strip was placed in 10 mL of 1% dilute sulfuric acid, allowed to stand at 40°C for 0.5 min, taken out and placed in 15 mL of 0.2 mol / L copper sulfate aqueous solution, allowed to stand at 40°C for 1 min, and taken out to obtain an iron-based amorphous-nanocrystalline dual-phase composite material prepared by a chemical precipitation method.
[0140] (2) Take 25 mL of 1000 mg / L methyl orange, orange II, methylene blue and rhodamine B dyes, add them to 150 mL of deionized water and mix them to obtain 250 mL of a 400 mg / L mixed azo dye aqueous solution, add 90 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 2.9, and place in a 25°C water bath and keep warm for 10 min.
[0141] (3) The mixed solution was mechanically stirred at 2000 r / min, 1 g of the iron-based amorphous-nanocrystalline dual-phase composite material (4 g / L) obtained in step (1) was added, the water bath temperature was maintained at 25°C, and 4.8 ml of the mixed azo dye aqueous solution was taken before and 0.5 min after the addition of the strips, respectively, and filtered through a 0.22 μ. aqueous polyethersulfone (PES) filter membrane.
[0142] (4) Add 0.4 mL of 1 g / L NaOH aqueous solution to the mixed azo dye aqueous solution that has been degraded for 0.5 min, filter at normal pressure using filter paper, wash the filtered 1 g of iron-based amorphous-nanocrystalline dual-phase composite material with deionized water, add it to the filtrate and place it in a 25°C water bath, continue stirring with a mechanical stirrer at 2000 rpm, and take 4.8 mL of the mixed azo dye aqueous solution at 1 min, 2 min, 3 min, 4 min, 5 min, and 10 min after re-adding the washed iron-based amorphous-nanocrystalline dual-phase composite material, respectively, and filter through a 0.22.2 water-based polyethersulfone (PES) filter membrane.
[0143] The solution spectrum was measured using a UV-visible photometer, and the color change of the dye solution over time was recorded by taking photos. The decolorization rate of the azo dye in the solution at different times was calculated and the decolorization rate curve was drawn.
[0144] The UV-visible absorption spectrum of this comparative example is as follows Fig.10 As shown in (a), the mixed azo dyes are rapidly degraded and decolorized under the degradation conditions. Fig.10 (b) It can be seen that after 0.5 minutes of reaction, the mixed azo dye has basically completed degradation, and its decolorization rate is 98.3%; after filtration, the decolorization rate of 400 mg / L azo dye reaches 98.2% at 3 minutes, and the decolorization rate reaches 97.3% at 5 minutes. After 10 minutes, the solution turns slightly red again, and the decolorization rate is reduced to 92.4%. The reason is that after the first degradation and precipitation filtration, no hydrogen peroxide and dilute sulfuric acid are added for secondary degradation. However, this comparative example can still prove that the (precipitation) filtration step can slow down the reverse reaction in the degradation process of high-concentration azo dyes, especially it can prevent the surface of the iron-based amorphous-nanocrystalline strips from being covered by (degradation product) precipitates, which may cause problems such as reduced decolorization rate or blackening of the solution, such as Fig.11 (b) Fig.12 (b) and Fig.13 (b) as shown.
[0145] On the one hand, filtering the precipitate in the aqueous solution after degradation can slow down the reverse reaction in the degradation process of azo dyes and maintain the degradation effect; on the other hand, since hydrogen peroxide and dilute sulfuric acid (to adjust the pH) were not added after the addition of NaOH, the formation of zero-valent iron on the surface of the strip and hydroxyl radicals in the aqueous solution were affected, so that the intermediate products formed by the azo dyes could not continue to degrade into CO 2 Small molecules such as azo dyes are removed, which inevitably causes a reverse reaction and regenerates a small amount of azo dye molecules in the solution, causing the decolorization rate to drop from 98.2% to 92.4%.
[0146] Comparative Example 2
[0147] In this comparative example, an iron-based amorphous-nanocrystalline dual-phase composite material was prepared from an iron-based amorphous strip by a chemical precipitation method, and then a mixed azo dye aqueous solution with a concentration of 320 mg / L was directly degraded without filtering or performing a secondary degradation treatment on the dye.
[0148] The specific steps are as follows:
[0149] (1) Same as Example 1,
[0150] (2) Take 20 mL of 1000 mg / L methyl orange, orange II, methylene blue and rhodamine B dyes, add them to 170 mL of deionized water and mix them to obtain a 320 mg / L azo dye aqueous solution, add 90 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place in a 25°C water bath and keep warm for 10 min.
[0151] (3) Using a mechanical stirring machine at 2000 r / min, the mixed solution was added with 1 g of the iron-based amorphous-nanocrystalline dual-phase composite material (4 g / L) obtained in step (1), the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before adding the strips and at 0.5 min, 1 min, 2 min, 3 min, 5 min, 6 min, 8 min, 9 min, and 15 min after adding the strips, respectively, and filtered through a 0.22 μ. aqueous polyethersulfone (PES) filter membrane.
[0152] The solution spectrum was measured using a UV-visible photometer, and the color change of the dye solution over time was recorded by taking photos. The decolorization rate of the azo dye in the solution at different times was calculated and the decolorization rate curve was drawn.
[0153] In this comparative example, there are no steps such as precipitation, filtration and further degradation. The UV-visible absorption spectrum is measured as follows: Fig.11 As shown in (a), the figure shows that the 320 mg / L mixed azo dye first degrades rapidly under the degradation conditions, and then the decolorization rate begins to decrease after 1 minute, and the reverse reaction of the azo dye degradation occurs. The reason for this phenomenon is that a large amount of organic precipitates are generated after the iron-based amorphous-nanocrystalline dual-phase composite material reacts with the high-concentration azo dye. It is necessary to filter out the precipitates in the aqueous solution and wash the strips (or select new strips) before degrading the filtrate again. Otherwise, the strip surface is covered with organic precipitates, the rate of producing zero-valent iron gradually slows down, and the generated intermediate product undergoes a reverse reaction and is converted back into azo dye, and finally reduces the azo dye decolorization rate; Fig.11 (b) It can be seen that the decolorization rate of the mixed azo dyes after 1 minute of reaction is 98.0%. However, as time goes by, without precipitation filtration and re-degradation, the decolorization rate of the mixed azo dyes gradually decreases, reaching 81.2% after 6 minutes of reaction and 67.8% after 15 minutes of reaction.
[0154] Comparative Examples 3 and 4 are used to illustrate that when commercially available iron-based amorphous strips are directly used to treat azo dyes with a concentration of 80 mg / L and above, the decolorization rate of the azo dyes is low and blackening occurs, such as Fig.12 and Fig.13 shown.
[0155] Comparative Example 3
[0156] This comparative example directly uses the commercially available iron-based amorphous strip to degrade the Orange II aqueous solution with a concentration of 80 mg / L.
[0157] The specific steps are as follows:
[0158] (1) Take 20 mL of 1000 mg / L Orange II solution, add it to 230 mL of deionized water, mix it and obtain 250 mL of 80 mg / L Orange II aqueous solution, add 90 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place it in a 25°C water bath and keep it warm for 10 min.
[0159] (2) The mixed solution was mechanically stirred at 2000 r / min, 1 g of commercially available iron-based amorphous ribbon (4 g / L) was added, the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before adding the ribbon and at 1 min, 2 min, 3 min, 5 min, 15 min, and 25 min after adding the ribbon, and filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane.
[0160] (3) Use a UV-visible photometer to measure the solution spectrum, take photos to record the color change of the dye solution over time, calculate the decolorization rate of the azo dye in the solution at different times and draw a decolorization rate curve.
[0161] The UV-visible absorption spectrum of this comparative example is as follows Fig.12 As shown in (a), the figure shows that the degradation rate of 80 mg / L Orange II aqueous solution is slow under this degradation condition. Fig.12 (b) It can be seen that after 5 minutes of reaction, the decolorization rate of Orange II is 87.4%, and the color of the aqueous solution gradually darkens; after 15 minutes and 25 minutes of reaction, the decolorization rates of Orange II aqueous solution are 87.0% and 86.8% respectively, and the color of the aqueous solution further turns black, showing a blackening phenomenon. It can be seen that the 4g / L commercially available 1K107 iron-based amorphous ribbon has limited ability to degrade 80mg / L Orange II aqueous solution.
[0162] Comparative Example 4
[0163] In this comparative example, the iron-based amorphous strips were directly used to directly degrade the Orange II aqueous solution with a concentration of 100 mg / L.
[0164] The specific steps are as follows:
[0165] (1) Take 25 mL of 1000 mg / L Orange II solution, add it to 225 mL of deionized water, mix it and obtain 250 mL of 100 mg / L Orange II aqueous solution, add 90 mmol / L hydrogen peroxide, add 5% by mass dilute sulfuric acid to adjust the pH to 3, and place it in a 25°C water bath and keep it warm for 10 min.
[0166] (2) The mixed solution was mechanically stirred at 2000 r / min, 1 g of commercially available iron-based amorphous ribbon (4 g / L) was added, the water bath temperature was maintained at 25°C, and 4.8 mL of the mixed azo dye aqueous solution was taken before adding the ribbon and at 1 min, 2 min, 3 min, 6 min, 9 min, 15 min, 25 min, and 45 min after adding the ribbon, and filtered through a 0.22 μm aqueous polyethersulfone (PES) filter membrane.
[0167] (3) Use a UV-visible photometer to measure the solution spectrum, take photos to record the color change of the dye solution over time, calculate the decolorization rate of the azo dye in the solution at different times and draw a decolorization rate curve.
[0168] The UV-visible absorption spectrum of this comparative example is as follows Fig.13 As shown in (a), the figure shows that the degradation degree and degradation rate of 100 mg / L Orange II aqueous solution under this degradation condition are low. Fig.13 (b) It can be seen that the decolorization rate of Orange II is 74.1% after 6 minutes of reaction; after 45 minutes of degradation, the decolorization rate is 71.4%. By comparing the Orange II aqueous solutions at 6 minutes and 45 minutes of degradation, it can be seen that the color of the azo dye aqueous solution becomes significantly darker after 45 minutes of degradation, and the blackening phenomenon is serious.
[0169] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for degrading azo dyes, characterized in that: The concentration of the azo dye is greater than 100 mg / L and less than 300 mg / L, and the degradation method comprises the following steps: The iron-based amorphous-nanocrystalline dual-phase composite material is placed in a solution containing an azo dye to achieve degradation of the azo dye; The iron-based amorphous-nanocrystalline dual-phase composite material is prepared by any one of methods 1 to 3: Method 1: soaking the iron-based amorphous strip in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material; Method 2: After pickling, the iron-based amorphous strip is immersed in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material; Method 3: Place the iron-based amorphous strip in a vacuum of not less than 5×10 -3 Pa vacuum environment, annealing at 450-900° C., cooling, and soaking in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material; The concentration of the copper salt aqueous solution in the methods 1 to 3 is 0.05-1.5 mol / L; the mass percentage of iron atoms in the iron-based amorphous strip is above 70%; The annealing time in the method 3 is 10-30min; The degradation temperature is 10-80° C., the pH is 2-6.5, and the concentration of hydrogen peroxide in the solution is 1-500 mmol / L.
2. The method for degrading azo dyes according to claim 1, characterized in that: The acid solution used for pickling in the second method includes one or more of sulfuric acid, hydrochloric acid, nitric acid and hypochlorous acid; the mass concentration of the acid solution is 1-30%.
3. A method for degrading azo dyes, characterized in that: The concentration of the azo dye is 300-1000 mg / L, and the degradation method comprises the following steps: placing the iron-based amorphous-nanocrystalline dual-phase composite material in a solution containing an azo dye, filtering after a first degradation, and then using the iron-based amorphous-nanocrystalline dual-phase composite material to perform a second degradation on the filtrate; The iron-based amorphous-nanocrystalline dual-phase composite material is prepared by any one of methods 1 to 3: Method 1: soaking the iron-based amorphous strip in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material; Method 2: After pickling, the iron-based amorphous strip is immersed in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material; Method 3: Place the iron-based amorphous strip in a vacuum of not less than 5×10 -3 Pa vacuum environment, annealing at 450-900° C., cooling, and soaking in a 10-80° C. copper salt aqueous solution to obtain the iron-based amorphous-nanocrystalline dual-phase composite material; The concentration of the copper salt aqueous solution in the methods 1 to 3 is 0.05-1.5 mol / L; the mass percentage of iron atoms in the iron-based amorphous strip is above 70%; The annealing time in the method 3 is 10-30min; The temperatures of the first degradation and the second degradation are both 10-80° C., the pH is both 2-6.5, and the concentration of hydrogen peroxide in the solution is both 1-500 mmol / L.
4. The method according to any one of claims 1 to 3, characterized in that: The azo dye includes any one or more of Orange II, methylene blue, rhodamine B, and methyl orange.
5. The method according to claim 3, characterized in that: The first degradation time is 30-600s.
6. The method according to claim 3, characterized in that: The filtration is carried out by one of normal pressure filtration, reduced pressure filtration or hot filtration; before the filtration, one or more of sodium hydroxide, sodium carbonate or sodium bicarbonate are added to form a precipitate.
Citation Information
Patent Citations
Modification method for preparing cobalt-based porous amorphous catalyst based on dealloying and application
CN114904530A
Method for improving catalytic degradation of reactive red 195 dye by FePC amorphous alloy and application
CN115041204A